Enhancing Academic Writing Skill Through Mini Lessons and Revision - Dorji, Jigme (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
An action research was conducted with class 12 science students (n=15) for three months with an aim of helping students improve their academic writing skill through mini revision lessons and feedback. The study was conducted based on pre-test-intervention-post-test design using mixed method. Test scores and interview were two main data collection tools. Data collected from test scores were analysed descriptively in percentage and average. Answers to interview questions were analysed thematically. Finding from the study revealed that students’ quality of writing improved proving the effectiveness of mini revision lessons and feedback.